TEM-fast small-loop soundings to map underground tunnels and galleries connecting the rock-hewn churches of Lalibela, Ethiopia - Ranieri, Gaetano; Haile, Tigistu; Alemayehu, Tamiru (Geoarchaeology, 2005)
As one of the first attempts to utilize the technique for intrasite archaeological prospection, a series of coincident square‐loop TEM‐fast geophysical surveys were carried out over the compounds of the largest of the rock‐hewn churches of Lalibela—Bete Maryam and Bete Amannuel—in North Ethiopia. Archaeologists have long believed that the different churches within each group were connected by underground tunnels. The aim of this survey was to identify, delineate, and map these underground channels and galleries. A total of 33 sounding surveys were conducted, the majority of which used a 3‐m‐side square loop. The survey traverses explored around the sides of the churches where underground connections to the other churches are possible. The results of the surveys, which are presented in terms of resistivity and depth pseudosections, clearly depict the presence of anomalies that could be associated with cavities, whose orientation suggests the presence of connecting galleries between the different churches. Whether these cavities were actually connecting galleries with religious implications or designed to be used as drainage paths remains a subject requiring further study involving additional geophysical investigations and physical excavation. © 2005 Wiley Periodicals, Inc.